Penerapan Teknik Naratif dalam Penulisan Naskah Video Feature “Kopi Nikmat Tantangan Hidup Sehat” - Zetira Nadia Rahmah; Encang Saefudin; Jimi Nurotama Mahameruaji (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Scriptwriters play an important role in effectively conveying messages and goals to the audience. A good script is able to build a logical storyline, convey a message implicitly and explicitly, and leave a deep impression on the audience. The goal to be achieved in writing this final project report is to explain the process of writing a script using narrative techniques in a feature video. In this final project, the script writing uses narrative techniques with a descriptive approach. In script writing, narrative techniques are applied in scripts as the main approach in building a structured storyline based on the attachment of cause-and-effect relationships between events. The narrative structure is divided into three stages, namely the preliminary stage (opening), the intermediate stage, and the closing stage (solution). The preliminary stage serves to introduce the phenomenon, the middle stage discusses the phenomenon more deeply, and the closing stage provides solutions to the problems raised. The application of this narrative technique proves that a good structure in scriptwriting is able to convey the message in a video feature effectively. The screenwriter has completed the tasks and roles in making an animated video entitled Kopi Nikmat Tantangan Hidup Sehat.